2007
DOI: 10.1063/1.2715864
|View full text |Cite
|
Sign up to set email alerts
|

Excitation of terahertz radiation by laser pulses in nonuniform plasma channels

Abstract: The excitation of terahertz radiation by laser pulses propagating in miniature plasma channels is considered. Generation of radiation by laser pulses in uniform plasmas is generally minimal. However, if one considers propagation in corrugated plasma channels, conditions for radiation generation can be met due to the inhomogeneity of the channel and the presence of guided waves with subluminal phase velocities. It is found that for channels and laser pulses with parameters that can be realized today, energy con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
45
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(49 citation statements)
references
References 17 publications
4
45
0
Order By: Relevance
“…The present scheme yields the THz field $10 5 kV/cm and the efficiency $10 À2 for the laser intensity $10 14 Terahertz (THz) radiation generation has become an exciting field of research due to its wide applications in material characterization, imaging, topography and remote sensing, 1 chemical and security identification, etc. 2,3 The researchers all over the world have been putting their efforts to achieve a THz radiation source with large electric field, [4][5][6][7][8][9][10][11][12][13][14][15][16][17] and several schemes have been proposed. THz radiation has been generated with the interaction of superluminous laser pulse with large band gap semiconductors and electro-optic crystals.…”
mentioning
confidence: 99%
“…The present scheme yields the THz field $10 5 kV/cm and the efficiency $10 À2 for the laser intensity $10 14 Terahertz (THz) radiation generation has become an exciting field of research due to its wide applications in material characterization, imaging, topography and remote sensing, 1 chemical and security identification, etc. 2,3 The researchers all over the world have been putting their efforts to achieve a THz radiation source with large electric field, [4][5][6][7][8][9][10][11][12][13][14][15][16][17] and several schemes have been proposed. THz radiation has been generated with the interaction of superluminous laser pulse with large band gap semiconductors and electro-optic crystals.…”
mentioning
confidence: 99%
“…Ponderomotive force and nonlinear process in laser plasma interaction are the main mechanisms of THz wave generation. Laser plasma interaction also offers the promise for generating coherent radiation (Nuss & Orenstein, 1997;Yampolsky & Frainman, 2006;Cheng et al, 2001;Antonsen et al, 2007;Gildenburg & Vvedenskii, 2007). For example, coherent pulses of THz radiation are especially of interest for time domain spectroscopy (Nuss & Orenstein, 1997).…”
Section: Introductionmentioning
confidence: 97%
“…Cheng et al (2001) have reported the generation of THz pulse radiation from plasma channels induced by femtosecond light strings, which are generated due to the establishment of a dipole moment in the channel by radiation pressure force of the light string, which oscillates at the plasma frequency and radiates. Antonsen et al (2007) proposed the employment of a corrugated plasma channel for phase matched THz radiation generation by the ponderomotive force of a laser pulse.…”
Section: Introductionmentioning
confidence: 99%
“…(2) is proportional to, and in phase with, the vector potential. The rate of energy transferred to the electromagnetic wave can be calculated as the power the ponderomotive force does on the plasma current 23 . It follows from this that the action,…”
Section: Spectral Shifting In Tenuous Plasmamentioning
confidence: 99%
“…As a laser pulse propagates through plasma, it loses energy by exciting plasma waves [2][3][4]19,23 .…”
Section: Spectral Shifting In Tenuous Plasmamentioning
confidence: 99%